Destination Image and Travel Motivation as Predictors of Revisit Intention: A Study of Domestic Tourists in Alor Island - Mesak Yamres Awang; Elia Maruli (Journal of Management and Entrepreneurship Research)
Objective: This study analyzes the effect of destination image interaction and domestic tourists' travel motivation in predicting the intention to revisit Alor Island. This study places travel motivation as a link between the interaction of a general tourist destination image and tourists' intention to revisit Alor Island. Research Design & Methods: The approach used in this study is a quantitative method, using a questionnaire distributed to 230 domestic tourists visiting Alor Island. The sample determination in this study follows the sample size guidelines for SEM-PLS analysis with a maximum likelihood estimation approach with a range between 100 and 250. Data analysis uses a structural equation approach with SPSS and SEM PLS to test the interaction of research variables and their indicators and explain the relationship between variable constructs. Findings: The results of the investigation found that destination image has an indirect impact on tourists' intention to revisit. In addition, travel motivation also directly affects the intention to revisit. It was also found that travel motivation mediates the effect of destination image on the intention to revisit. Implications and Recommendations: This study shows that building a positive destination image through promotion, facilities, and cultural uniqueness can motivate tourists to return. Therefore, the tourism industry must provide quality services, develop authentic and sustainable tourism experiences, and utilize technology and market segmentation. Contribution & Value Added: Travel motivation fully mediates the impact of destination image and tourists' intention to revisit the Alor Island tourist destination. Culture, history, entertainment, social interaction, and access to information can increase tourists' intention to revisit.